Do Demographic Factors affect Glass Ceiling Perception of Women in Bank and Financial Institutions (BFIs) of Nepal? (Pravaha, 2025)
In this competitive business world, still women perceive the continuation of the glass ceiling. Some demographic variables of women also seemed to influence their perception of the glass ceiling (GC). Therefore, the study examined how demographic characteristics impact women's perceptions of the GC in Nepalese banks and financial institutions (BFIs). The population of the study consisted of women holding positions from supervisor to senior manager in BFIs. BFIs were divided into three strata such as commercial banks, development banks, and finance companies. Information from 403 women was collected using purposive sampling. A descriptive cum analytical research design was used, using statistical tests like frequency, mean, and One-Way ANOVA, and an independent sample t-test. The outcome demonstrated that, except for education, demographic characteristics (marital status, age, position, income, women with children, and organization types) affect how women perceive the GC. The GC perception of women in financial institutions differed on average; however, there was no difference in between financial institutions, according to post hoc analysis. This study will assist organizations in understanding how women's perceptions of the GC are influenced by demographic considerations. The study's limitation is that it only looks at the perception of the GC in the organizational context.